2012
DOI: 10.1002/pits.21630
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the cognitive abilities of culturally and linguistically diverse students: Predictive validity of verbal, quantitative, and nonverbal tests

Abstract: Verbal and quantitative reasoning tests provide valuable information about cognitive abilities that are important to academic success. Information about these abilities may be particularly valuable to teachers of students who are English‐language learners (ELL), because leveraging reasoning skills to support comprehension is a critical aptitude for their academic success. However, due to concerns about cultural bias, many researchers advise exclusive use of nonverbal tests with ELL students despite a lack of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 22 publications
(33 reference statements)
1
16
0
Order By: Relevance
“…The authors suggested that these nonverbal assessments were not a valid or reliable way to assess for giftedness for students who were ELL and that the nonverbal assessments may be less valid for this subgroup of students (Lohman, Korb, & Lakin, 2008). Lakin (2012) found similar results in another study. The verbal reasoning and quantitative reasoning subtests of the CogAT assessment (a group administered test) were shown to be better indicators of future academic achievement for the students who were ELL when compared to the nonverbal assessments.…”
Section: Nonverbal Testssupporting
confidence: 83%
See 3 more Smart Citations
“…The authors suggested that these nonverbal assessments were not a valid or reliable way to assess for giftedness for students who were ELL and that the nonverbal assessments may be less valid for this subgroup of students (Lohman, Korb, & Lakin, 2008). Lakin (2012) found similar results in another study. The verbal reasoning and quantitative reasoning subtests of the CogAT assessment (a group administered test) were shown to be better indicators of future academic achievement for the students who were ELL when compared to the nonverbal assessments.…”
Section: Nonverbal Testssupporting
confidence: 83%
“…The measures in this study were the CogAT (verbal, nonverbal, and quantitative reasoning batteries) and the Arizona Instrument to Measure Standards Dual Purpose Assessment (AIMS DPA) (reading/language arts and math subtests). Lakin (2012) found that the largest differences in scores between the students who were ELL and the students who were not ELL were in the verbal reasoning and math areas of the assessment. For all of the students, there were high correlations between Summary.…”
Section: Nonverbal Testsmentioning
confidence: 96%
See 2 more Smart Citations
“…When investigating nonverbal aptitude tests, the most commonly mentioned tests are the NNAT, the Wechsler Battery, and the CogAT. The biggest difference between the three is that the NNAT is the only one of the three that is comprised exclusively of nonverbal components, whereas the CogAT and the Wechsler battery both have verbal and quantitative elements that help to comprise the test (Lakin, 2012;Wechsler, 2003). Giessman et al (2013) analyzed data from one particular mid-Western school district to gauge the NNAT2 and the Cognitive Ability Test 6 (CogAT6) to predict the score a student would achieve on the WISC-IV, or one of the Wechsler batteries for assessing student intelligence.…”
Section: Critique Of Previous Researchmentioning
confidence: 99%